Evaluation of transversal force influence in layers of reinforced concrete with survival moulds/Sluoksniuotųjų gelžbetoninių konstrukcijų su liktiniais klojiniais stiprumo skersinių jėgų atžvilgiu įvertinimas - Bistrickaitė, Rėda; Žilinskas, Romualdas (Journal of Civil Engineering and Management, 2001)
Bending composite reinforced concrete slabs have horizontal concreting joints and this is their main difference from monolithic constructions. During initial bending stage of loaded composition slab compression and shear stresses appear, therefore they should be treated as monolithic ones. Nevertheless, with the augmentation of deflection the influence of transversal forces increases. Depending on the distance between concentrated force and support force, corresponding shear stresses are caused in the contact zone of the layered slab. Vector trajectories of those stresses correspond to the curve of compression layers in imaginary internal arches. The distance between the support and shear force, and the number of repetitive static heights (a =1… 2… 5d) of the slab have been evaluated, some cases have been observed and noted when forces influencing the detachment of monolithic and precast slab are the greatest ones. It has been noticed that the augmentation of distance between the support and vertical force causes the decrease of leaning angle of successive shear stresses in reinforcement bars.Article in Lithuanian.First Published Online: 30 Jul 2012